Strategi Pengelolaan Aset pemerintah Provinsi Jawa Timur untuk Meningkatkan PAD di UPT BLK Jember - Refi Mariska; Riza Umami; Sofiah Sofiah (Lembaga Pengembangan Kinerja Dosen, 2025)
Utilizing local government assets is one of the most important ways to increase local revenue. Optimizing assets not only increases Regional Original Income (PAD) but also promotes efficient public services and strengthens transparent and accountable governance. In this context, assets managed by Technical Implementation Units (UPTs), such as the Vocational Training Centers (BLKs), have significant potential to be optimized as skills training centers and economically productive units. The purpose of this study is to identify barriers and strategies that can be used to maximize the utilization of East Java Provincial Government assets managed by the UPT BLK Jember. The method used in this study is a descriptive qualitative approach involving data collection through in-depth interviews, field observations, and documentation collection. The data analysis process is carried out in three stages: data reduction, data presentation, and conclusion drawing. The research findings indicate that the main challenges in asset utilization at the UPT BLK Jember include limited digitalization systems, inadequate physical conditions of assets, weak internal coordination, and less strategic asset locations. Furthermore, minimal promotion of training services and the lack of community and business involvement also hinder optimal asset utilization. To address these challenges, this study proposes four main strategies, namely: (1) digitizing asset management to make it more transparent and efficient; (2) increasing human resource capacity, particularly in asset management and vocational training; (3) establishing collaboration with third parties such as private training institutions and the industrial world; and (4) implementing a social marketing-based communication strategy to increase the visibility of BLK in the community.